2019
DOI: 10.1016/j.jsps.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Alpina officinarum Hance, chemically and biologically

Abstract: Alpinia officinarum Hance is one of the most commonly used herbs belongs to Family Zingiberaceae. The current work deals with the qualitative and quantitative chemical study of this plant rhizomes in addition to the investigation of its anticancer activities. The results of the qualitative analysis showed a variation of phytochemical contents in this plant. While quantitative analysis showed a very promising percentage of active materials and Pharmacopeial constants. Analysis of elements like Cu, Zn & Mg were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The phenolic content and antioxidant activity in AOP may be responsible for the increased antioxidant activity of supplemented cheese. These results were in agreement with Housman et al, (2014) and Alasmary et al, (2019). Table 6, showed, also, that adding AOP to cheese was accompanied by high amounts of dietary fibers, because AOP has a higher dietary fiber content, 16.6 % (Gazal et al, 2014 andTang et al, 2018).…”
Section: Resultssupporting
confidence: 85%
“…The phenolic content and antioxidant activity in AOP may be responsible for the increased antioxidant activity of supplemented cheese. These results were in agreement with Housman et al, (2014) and Alasmary et al, (2019). Table 6, showed, also, that adding AOP to cheese was accompanied by high amounts of dietary fibers, because AOP has a higher dietary fiber content, 16.6 % (Gazal et al, 2014 andTang et al, 2018).…”
Section: Resultssupporting
confidence: 85%
“…One such herb is Alpinia officinarum Hance that is known as the smaller galangal. A. officinarum Hance belongs to the Zingiberaceae family and is widely cultivated in southern China and many Asian countries [3]. The rhizomes of A. officinarum Hance have been used as a traditional medicine to relieve stomachache, to invigorate circulation, treat colds, and to reduce swelling for over 1000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed three major groups of chemical constituents isolated from the rhizomes of the smaller galangal, including flavonoids, glycosides and diarylheptanoids [5]. Recently, pharmacological activities of these phytochemicals have been reported, including anti-inflammatory, antioxidant, and anticancer effects [3,6,7]. Nevertheless, the current literature is limited with respect to the bacteriostatic activity of the herb rhizomes.…”
Section: Introductionmentioning
confidence: 99%
“…The oral median lethal dose (LD 50 ) of the investigated alcohol extract determined at doses up to 4000 mg/kg ( Alasmary et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%